2015
DOI: 10.4238/2015.september.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the AIB1 protein in the proliferation and transformation of human esophageal squamous cell carcinoma

Li L1,
et al.

Abstract: ABSTRACT. The aim of this study was to investigate the expression of AIB1 in human esophageal squamous cell carcinoma and its correlation with Ki67 expression. The immunohistochemical method streptavidinperosidase was used to analyze the expression of AIB1 and Ki67 in specimens from 60 patients with esophageal squamous cell carcinoma and in 20 control individuals with normal esophageal tissue. Expression correlation, clinical significance, and relationships between the two groups were determined. In the 20 ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…It was also demonstrated that in ESCC, KAT3B and KAT3A/CREBBP (CREB binding protein) harboured frequent inactivating mutations [43]. KAT13B/AIB1 (amplified in breast cancer 1) was overexpressed in ESCC in comparison with adjacent normal tissue [44] and its expression was positively associated with advanced clinical stage, distant lymph node metastasis and chemoradiotherapy resistance in ESCC [44][45][46][47]. Overexpression of KAT13B was linked with poor overall, disease-specific, and progression-free survival and was shown to be an independent predictor factor [45,47].…”
Section: Histone Acetyltransferasesmentioning
confidence: 99%
“…It was also demonstrated that in ESCC, KAT3B and KAT3A/CREBBP (CREB binding protein) harboured frequent inactivating mutations [43]. KAT13B/AIB1 (amplified in breast cancer 1) was overexpressed in ESCC in comparison with adjacent normal tissue [44] and its expression was positively associated with advanced clinical stage, distant lymph node metastasis and chemoradiotherapy resistance in ESCC [44][45][46][47]. Overexpression of KAT13B was linked with poor overall, disease-specific, and progression-free survival and was shown to be an independent predictor factor [45,47].…”
Section: Histone Acetyltransferasesmentioning
confidence: 99%